A nonparametric method for valuing new goods - Laura Blow; Ian Crawford (European Central Bank (ECB), 2002)
This paper presents a revealed preference method for calculating a lower bound on the virtual or reservation price of a new good and suggests a way to improve these bounds by using budget expansion paths. This allows the calculation of cost-of-living and price indices when the number of goods available changes between periods. We apply this technique to the UK National Lottery and illustrate the effects of its inclusion in measures of inflation.
Keywords: C43; D11; 330